Influence of water availability and grapevine phenological stage on the spatial variation in soil respiration. (19th April 2017) - Hernández‐Montes, E.; Escalona, J.M.; Tomás, M.; Medrano, H.
Abstract: Background and Aims: An understanding of spatial variation in soil respiration is critical to determining the carbon balance in grapevines. The effect of soil water content on soil respiration during different phenological stages in two grapevine cultivars, Grenache and Tempranillo, was studied over two seasons (2013 and 2014). Methods and Results: Soil respiration was measured from five locations confined to within and between rows of vines at five phenological stages between budburst and postharvest under irrigated and non‐irrigated conditions. Vine phenology influenced the in‐row soil CO2 efflux to a greater extent than the between‐row CO2 efflux, while irrigation resulted in in‐row soil respiration 65% higher than that of the between‐row positions. In contrast, the flux from the in‐row positions of the non‐irrigated treatment was only 25% higher than that of the between‐row positions. Soil moisture and vine phenological stages appeared to have a greater influence on soil respiration than soil temperature. Conclusions: Significant correlations existed among soil respiration, irrigation and the vine phenological stages. Soil respiration increased from budburst to pea‐size berry stage; thereafter, it decreased until the ripening stage before increasing again during the postharvest stage. Significance of the Study: The study showed that soil water availability and vine phenology play an important role in influencing soil respiration under field conditions.